The owner’s representative role in South African mining construction projects - Mrara, Bongani (My University, 2013)
The owner’s representative role has been identified as a means for project owners to improve the chances of success for their projects. Projects are an important means for mining companies to develop new resources or to extend the lives of their existing resources; however, little research has been performed into the owner’s representative role in the mining industry. The research objective was to describe the owner’s representative role in the South African mining industry, specifically in relation to the responsibilities of the owner’s representative, the characteristics, the owner’s organisation factors and the project factors impacting on the role. A list of propositions was developed, based on a literature review of the practice of the role in general industry. A survey was developed and tested on a sample of project professionals in the South African mining industry to test the propositions, as well as to determine the particular application of the role in the South African mining industry. It was found that that the responsibilities, characteristics and factors impacting on the role are similar to those in world literature, except for minor modifications. However, there were inconsistencies in the application in the South African mining industry, between the application of the role and owner’s organisation and project factors prevalent in mining companies. The key message is that owners should perform an analysis of the project environment, including a review of organisation and project factors that may impact on the owner’s representative role, before selecting an owner’s representative.
MBA thesis
Keywords: Mines and mining; Mining construction